Cabin safety sensitivity to the mechanical parameters of the main crashworthy stages - Astori, P.; Ramachandran, T. (My University, 2018)
Crashworthy helicopters have energy absorbing concepts introduced into seats, subfloor and landing gears. These stages are always passive systems, usually triggered by a load level, and develop pre-set responses independently from the crash speed. Moreover, the different stages are usually studied as single components, without considering the mutual effects and any possible integration. This study is based on a lumped mass numerical model of a representative, but very simplified, rotorcraft section, including the three crashworthy stages of landing gear, subfloor structure and seat with anthropomorphic dummy. A series of analyses show the advantages, in terms of accident survivability, associated to a seat and landing gear with mechanical characteristics optimised according to varying impact velocities.